Pedagogical Analysis of Child Education Methods in Tarbiyatul Aulad and Their Relevance to Contemporary Islamic Education - Rahmah, Faizah Nur (Journal Of Islamic Education And Pesantren, 2023)
This study aims to provide a pedagogical analysis of child education methods presented in Tarbiyatul Aulad fil Islam by Abdullah Nashih Ulwan and to examine their relevance to contemporary Islamic education. The study is grounded in the need to reconstruct child education methodologies that are not merely normative-theological but also adaptive to social dynamics, child psychological development, and the challenges of the digital era. Employing a qualitative approach with a library research design, this study utilizes content analysis of the primary text alongside relevant literature in Islamic pedagogy and modern educational theory. The findings reveal that the child education methods in Tarbiyatul Aulad are holistic and integrative, encompassing role modeling (uswah), habituation (ta‘wid), advice (mau‘izhah), supervision (muraqabah), and educative discipline (ta’dib). These methods collectively form a pedagogical framework that integrates spiritual, moral, intellectual, and social dimensions in shaping children’s personality. Analytically, these methods demonstrate conceptual convergence with social learning theory, behaviorism, and humanistic educational approaches. Nevertheless, certain concepts require contextual reinterpretation to align with child-friendly educational paradigms, digital literacy, and reflective-critical approaches within contemporary Islamic education. The study concludes that the child education methods in Tarbiyatul Aulad make a significant conceptual contribution to the development of contemporary Islamic pedagogy, provided that they are contextualized through a dialogical engagement between normative tradition and modern educational theory. These findings enrich the discourse of Islamic pedagogy and offer a conceptual foundation for strengthening value-based character education within contemporary Islamic educational systems.